Institutional Anomie Theory and Cybercrime—Cybercrime and the American Dream, Now Available Online - Dearden, Thomas E. (Journal of contemporary criminal justice, 2021)
As the world becomes increasingly connected and interdependent upon technology, crimes are moving online. Research on cybercrime is beginning to test the applicability of traditional criminological theories for understanding crime in this new medium. Using a national sample of 215 self-admitted cybercriminals, we examine Messner and Rosenfeld’s institutional anomie theory. Negative binomial regressions reveal that expressed levels of institutional anomie correlate with increased cybercrime activity. A curvilinear relationship was found, such that low and high levels of institutional anomie lead to higher levels of cybercrime. Our findings reveal how the dark side of the American Dream can lead to online criminality. Specifically, the penetration of, and accommodation to economic values dictated by American capitalism can lead individuals to adopt values such as the fetishism of money that, in turn, affects their online behavior and criminality.